Perbaikan Kualitas Pelayanan Berdasarkan Bauran Pemasaran Di Assalaam Hypermarket - Arita, Al Fara Dila Ika, Ir. Muchlison Anis, MT, Hafidh Munawir, S.T., M.Eng (2016)
Competition of business in the world is getting stronger. Almost all company improve their performance dan quality to be able than others dan get a maximum profit. Similarly, business in retail is growing more rapidly, they are tryimg to get more customers. For that activities to inccrease customers, a retail should be able to know their performance and quality. It needs measurement their performance and quality, one of indicator is service quality. Service quality to be if the company able to make customers feel satisfied with their performance. Parameter that is used to measure customer satisfaction here is 7P that is Product, Price, Place, Promotion, People, Process, dan Physical Evidence. Based on the method the attributes in quadrant A need to be repaired because it has low of level saticfaction and high in interest level. Atributes 15, 19, 30, 35 and 38 must be in analysis and improvements with Six Sigma. Six sigma help to find root couse of problems and solutions to solve it. So it can be applied in Assalaam Hypermrket. The level of customers satisfaction at 64,21% that mean they get enough of satisfaction and the do the improvement an the level of customers satisfaction to be 67,25%. It means level of customers satisfaction increase by 3,03%.